Robotic mist bath wheelchair: innovations in automated body drying and sanitization for improved patient hygiene - Vijay Mahadeo Mane; Harshal Ambadas Durge; Chin-Shiuh Shieh; Rajesh Dey; Rupali Atul Mahajan; Siddharth Bhorge (IAES International Journal of Robotics and Automation (IJRA), 2025)
This paper presents the development and evaluation of the robotic mist bath wheelchair (MBWC), a multifunctional assistive device designed to enhance hygiene and comfort for individuals with limited mobility. The MBWC integrates mist-based bathing, automated sanitization, and warm air-drying into a compact, wheelchair-mounted system suitable for home and clinical settings. Experimental evaluations demonstrated effective temperature maintenance and a 30% reduction in bathing time compared to conventional methods. User trials with 20 participants indicated a 92% satisfaction rate, reflecting improvements in hygiene, comfort, and operational ease. MBWC provides a cost-effective, hygienic alternative to traditional bathing methods, addressing critical challenges in eldercare and rehabilitation environments.